Le palmier dattier en Tunisie : Un secteur en pleine expansion - Rhouma A. (Le palmier dattier dans l'agriculture d'oasis des pays méditerranéens, 1993)
The date palm tree has a very important role in south Tunisia, both from the socio-economic and ecological viewpoint. It is the basis of the economy in the regions of Djerid and Nefzaoua and it is in a privileged position in the national economy. Tunisian palm groves cover an area of 22,500 ha, with around 3,000,000 trees. They assure a rather irregular production, but in good evolution, from 85 to 90,000 tons. The contribution of a variety called 'Deglet Nour', in number and production, is very important, 56 per cent and 60.5 per cent respectively. The development of the sector aims at quantity, quality and perpetuity of production and is linked to three major problems: irrigation water, management system and the relative lack of scientific and technical references considered reliable and worth spreading in the sector. The date market is efficient, quite complicated and risky. Exports (25-30 per cent of the production), mainly to the EC countries, are also quite irregular but in full expansion. The Tunisian date sector, although seriously threatened by the Bayoud and also subject to some social-ecological-technical problems, is a promising sector. All Tunisian actors are aware of it. Actions are planned at research, information, spreading and development level in order to preserve the oasian patrimony, improve and valuate the production capacity for a better profitability and marketing.
Journées Internationales d'Elche sur le Palmier Dattier dans L'Agriculture d'Oasis des Pays Méditerranéens, 25-27 Apr 1995, Elche (Spain)